The apparent paradox of abundant foramol facies in low latitudes: their environmental significance and effect on platform development - Wilson, Moyra; Vecsei, A. (Elsevier, 2005)
Recent studies of low-latitude carbonates from SE Asia and Australia have revealed deposits and platform-types that do not fit easily into the perceived view of dwarm-waterT tropical carbonates. The sediments are classified as a foramol or foralgal facies, and are dominated by non-framework building, light-dependent biota such as perforate larger benthic foraminifera, coralline algae and sometimes Halimeda. Although ancient foramol deposits are often interpreted as an indication of non-tropical conditions, for amolfacies have long been known from the tropics, yet the environmental conditions in which they form are poorly known. The aims of this paper are to evaluate how these deposits are best classified, and more importantly whether there are any overriding controls that influence their common development in low-latitude areas, and if resultant platform development is affected. The deposits are all best grouped within the Photozoan Association [James, N.P., 1997. The cool-water depositional realm. In:James, N.P., Clarke, J.A.D., (Eds.), Cool-Water Carbonates. SEPM Special Publication 56, 1-20], an assignment synonymous with warm water conditions. The facies were also found to develop in conditions of limited light, or oligophoty.All the platforms described are characterised by having extensive areas of doligophotic T facies, generally in water depths extending down from 20m, but sometimes in shallower waters. Platforms types vary from land-attached rimmed shelves, homoclinal and distally steepened ramps, to isolated banks and platforms, but all have extensive moderate to deep photic zone development of oligophotic facies. Some workers might assign these platforms to the dincipiently drowned T platform-type [Read, J.F., 1985. Carbonate platform facies models. American Association of Petroleum Geologists Bulletin 69, 1-21]. However, a morphological assignment is preferred here to signify that many of the deposits did not, or may not, form through drowning. Limited light in moderate to deeper depths of the photic zone, often in regions with a reduced depth euphotic (high light) zone is seen as key to the extensive development of these deposits and the resultant platforms. These conditions are often developed in humid low-latitude areas of high terrestrial runoff (and therefore regions of reduced water salinity), or in areas of nutrient upwelling. Reduced water clarity due to nutrients, plankton blooms, suspended particulate matter, upwelling and strong currents all promote the development of oligophotic conditions and facies on a regional scale. Time periods of relative rises in sea level can also promote oligophotic facies development. The findings of this study have broader implications for the development of low-latitude platforms beyond Australasia, and during time periods when non-framework building, oligophotic biota are dominant sediment contributors. The reconstruction of past climatic conditions based on study of foramol grain assemblages requires careful study to distinguish warm water deposits from those formed in cool waters.